A randomized controlled trial for measuring effects on cognitive functions of adding ketamine to propofol during sedation for colonoscopy. Issue 36 (4th September 2020) - Tian, Liang; Luan, Hengfei; Zhu, Pin; Zhang, Zhiyuan; Bao, Hongguang
Abstract: Background: The purpose of this study was to evaluate the effects of adding ketamine to propofol on cognitive functions in patients undergoing sedation for colonoscopy. Methods: In this randomized, double-blinded, and controlled study, 200 patients were randomly allocated to ketamine/propofol admixture group (Group KP, n = 100), and propofol group (Group P, n = 100). Patients in Group KP received 0.25 mg/kg of ketamine and 0.5 mg/kg of propofol. Patients in Group P received 0.5 mg/kg propofol. Cognitive functions were measured using CogState battery before and after the colonoscopy procedure. Ninety five patients in Group KP and 92 patients in Group P had completed the CogStates tests and were included in the data analysis. Results: Compared with before procedure baseline, the performance on detection and identification tasks were significantly impaired after the procedure in both Group KP ( P = .004, P = .001) and Group P patients ( P = .005, P < .001). However, one-card learning accuracy and One-back memory was only impaired in Group KP patients ( P = .006, P = .040) after the endoscopy but left intact in Group P patients. Group KP patients showed more severe impairment in one-card learning accuracy compared with Group P patients ( P = .044). Group KP patients have better 5 minutes MAP ( P = .005) and were also less likely to suffer from complications such as respiratory depression ( P = .023) and hypotension ( P = .015). OAA/S scores, BIS, MAP, complications, recovery times, and endoscopist and patient satisfaction were similar between the 2 groups. Conclusion: Although adding ketamine to propofol for sedation in colonoscopy provided fewer complications such as respiratory depression and hypotension, it also causes more impairment in cognitive functions.